Analisis Investasi, Pendapatan Asli Daerah, Tenaga Kerja dan Pertumbuhan Ekonomi: Studi Provinsi Jawa Barat - Riyadi, Muhammad Danan; Woyanti, Nenik (Universitas Muhammadiyah Semarang, 2022)
Economic growth is one of the important indicators to analyze a national development that occurs in a country or region. This can be seen from the increase in Gross Regional Domestic Product (GRDP) and its relationship with the level of regional independence and the quality of human resources in a region. The high rate of economic growth as indicated by the high value of GRDP indicates that the region is progressing in the economy. This study aims to analyze the effect of Investment, Local Own-source Revenue (PAD), Labor, and Human Development Index (HDI) on Economic Growth in the Regency/City of West Java Province. This study uses secondary data sourced from the Central Bureau of Statistics (BPS) and the Indonesia Investment Coordinating Board (BKPM), with cross-sectional data consisting of 18 regencies and 9 cities in West Java Province and time-series data from 2015 – 2019. The analytical method used is panel data regression with Fixed Effect Model (FEM). The results of the study prove that there is a positive (simultaneous) effect between Economic Growth and PAD, Labor, and also HDI, while Investment has a negative effect on Economic Growth in the Regency/City of West Java Province. While partially, the PAD and HDI variables have a positive and significant effect on economic growth, but the Labor variable has a positive but not significant effect on Economic Growth in the Regency/City of West Java Province. Meanwhile, the Investment Variable has a negative but not significant effect on Economic Growth in the Regency/City of West Java Province.